2020
DOI: 10.1371/journal.pone.0235178
|View full text |Cite
|
Sign up to set email alerts
|

HIV prevalence and the cascade of care in five South African correctional facilities

Abstract: Background South Africa is home to the world's largest HIV epidemic. Throughout the world, incarcerated individuals have a higher prevalence of HIV than the general public, and South Africa has one of the highest rates of incarceration in sub-Saharan Africa. In spite of this, little has been published about the burden of HIV and how care is delivered in South African correctional facilities. Objective To estimate the prevalence of people living with HIV and identify initiation and retention in the HIV cascade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The HIV prevalence estimates reported in peer‐reviewed academic journals consistently reported higher prevalence estimates relative to what was reported in the UNAIDS report. A systematic review published in the Lancet in 2016 reported prevalence estimates ranging from 4.2% (Ethiopia) to 23.0% (Malawi) in East Africa, 7.2% (South Africa) to 34.9% (Swaziland) in Southern Africa and 2.3% (Ghana) to 10.2% (Congo) in West and Central Africa [7] Additionally, a cross‐sectional study of five correctional facilities across South Africa estimated that the HIV prevalence among prisoners was 17.7% (95% CI = 17.2% to 18.3%) [73].…”
Section: Resultsmentioning
confidence: 99%
“…The HIV prevalence estimates reported in peer‐reviewed academic journals consistently reported higher prevalence estimates relative to what was reported in the UNAIDS report. A systematic review published in the Lancet in 2016 reported prevalence estimates ranging from 4.2% (Ethiopia) to 23.0% (Malawi) in East Africa, 7.2% (South Africa) to 34.9% (Swaziland) in Southern Africa and 2.3% (Ghana) to 10.2% (Congo) in West and Central Africa [7] Additionally, a cross‐sectional study of five correctional facilities across South Africa estimated that the HIV prevalence among prisoners was 17.7% (95% CI = 17.2% to 18.3%) [73].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies assessed interventions involving screening campaigns that estimated the prevalence of HIV in prisons across different countries. 8,17,24,26,34,36 On the one hand, the studies suggest weak HIV infection control practices in SSA prisons in terms of screening at entry, during incarceration, and at exit from prison. This is reflected in the low proportion of inmates who knew their HIV status prior to screening.…”
Section: Screening For Hivmentioning
confidence: 99%
“…Other countries in sub-Saharan Africa with results involving multiple correctional facilities report TB prevalence ranging from 457 to 888 per 100 000 population. [23][24][25] However, a direct comparison to the prevalence reported in the other countries can not be done due to differences in definitions of TB used and differences in prevalence in the general population.…”
Section: Study Findings In Relation To Other Studiesmentioning
confidence: 99%